The Analysis of Content of Heavy Metals Cadmium (cd) in the Flow of the River Barumun Labuhanbatu Selatan - Sri Kedaton; Arman Harahap (Budapest International Research and Critics University, 2021)
The number of community activities in the area of River Barumun Labuhanbatu South will produce heavy metals in the waters and will accumulate to the bottom of the waters in the sediment. This study discusses the content of heavy metal Cd in sungai Barumun Labuhanbatu Selatan. The research was conducted in December 2020 until January 2021 in the region of the waters of the River Barumun Labuhanbatu Selatan. The process of sampling using purposive sampling method. Data analysis was done descriptively by looking at the results of the measurements of some parameters of the waters and the test results of water samples in the laboratory by comparing the quality standard according to the Decision of the Minister of Environment No. 51 Year 2004. As for the test sediment samples in the laboratory compared with the raw quality of the concentration of heavy metals in the sediment IADC/CEDA 1997. The results of the heavy metal concentration of Cd in the surface water ranged 0,003-0,068 mg/l, the concentration of heavy metal cadmium in water depth of 5 meters has a range of 0.007-to 0.058 mg/l.